How World-Class Universities Affect Global Higher Education
VIII, 204 p.
Keywords: World-class universities, commonly recognized as global research universities or flagship universities, are cornerstone institutions embedded in any academic system and play an important role in developing a nation’s competitiveness in the global knowledge economy. The development of world-class universities is high on the policy agenda of various stakeholders across the globe. In the past few years, an increasing number of nations, regions and higher education institutions in both developed and developing countries have joined the same race for academic excellence and have adopted a range of development strategies and implemented various reforms. From a comparative perspective, How World-Class Universities Affect Global Higher Education intends to provide an in-depth picture of excellence initiatives and relevant policies adopted in various nations and regions, and to reflect opportunities and challenges of developing excellence.